Microscopic comparative study of the exposure effects of testosterone cypionate and ethinylestradiol during prenatal life on the prostatic tissue of adult gerbils - Perez, Ana P. S.; Biancardi, Manoel F.; Vilamaior, Patricia S. L.; Goes, Rejane M.; Santos, Fernanda C. A.; Taboga, Sebastiao R. [UNESP] (Wiley-Blackwell, 2012)
There is an increasing variety of endocrine disrupting chemicals (EDCs) either with (anti)estrogenic or (anti)androgenic potential widely present in the environment. These xenosteroids may mimic endogenous steroid hormones disrupting the homeostasis of physiological pathways and leading to several disturbances, especially in tissues highly dependent on steroid hormones such as the prostate. Taking this into account, this comparative study aimed to verify the potential of ethinylestradiol (EE) and testosterone acting as ECDs on the prostate of both male and female adult gerbils exposed to these agents during the embryonic phase. Consequently, pregnant gerbils were treated either with 10 mu g/kg/day of EE or with a single dose of 1 mg of testosterone cypionate. The pups that were born 68 days after testosterone exposure and the pups that were born after 3 days of EE exposure were allowed to grow but were sacrificed within 4 months. Serological, morphological, stereological, and immunohistochemical analyses were used. Overall, the results showed that both sexes exposed to testosterone and EE during gestation had a prostatic gland with an increased stromal and epithelial and a reduced luminal compartment. Moreover, we observed that glands affected with prostatic intraepithelial neoplasia showed intense stromal reshuffling. In conclusion, although these alterations were observed in both sexes, more relevant to this study was the differential responsiveness of males and females exposed to these different drugs. Whereas the EE affected males more, the testosterone was more harmful to the females. Microsc. Res. Tech. 75:10841092, 2012. (c) 2012 Wiley Periodicals, Inc.
Keywords: ethinylestradiol; testosterone; ventral prostate; female prostate; gerbil; endocrine disrupting chemicals